Understanding the relationship between education-based hypergamy and women's social interaction in China: mediating roles of career aspirations and social distrust - Penghui Wu; Ming Zhang; Senhao Xiong (Frontiers in Public Health)
BackgroundEducation-based hypergamy (EBH) is a key factor influencing the social interaction (SI) of women in China. Women in education-based hypergamous marriages, where they have lower education levels than their spouses, often face unique challenges that may impact their social lives. The dynamics of traditional gender norms and opportunity costs of balancing career and household duties present barriers to SI for these women. Thus, understanding the mechanisms that mediate and moderate this relationship is crucial for addressing social inequalities and improving public health outcomes.MethodsData for this study were obtained from the 2021 Chinese General Social Survey (CGSS), which sampled 1,442 women. We employed a mediation effect testing model to examine the relationships among EBH, career aspirations (CA), social distrust (SD), and SI. The model also tested the moderating role of household income in mitigating the effects of EBH on SI.ResultsThis study first highlights that EBH is negatively associated with women's SI. Notably, household income moderated this relationship, with higher income levels alleviating the negative impact of EBH on SI. Additionally, CA and SD were found to mediate the relationship between EBH and SI, demonstrating that these factors contribute to the reduction in SI among women in education-based hypergamous marriages.Discussion/conclusionThese findings partially align with prior research on gender norms and social interaction, offering theoretical insights into the negative effects of EBH on women's SI. From a public health perspective, the results underscore the need for policies that enhance household income and provide flexible work arrangements. Such policies could reduce the constraints imposed by EBH, thereby promoting better social interaction, mental well-being, and overall health for women.